2020 29th IEEE International Conference on Robot and Human Interactive Communication (RO-MAN) 2020
DOI: 10.1109/ro-man47096.2020.9223449
|View full text |Cite
|
Sign up to set email alerts
|

How context shapes the appropriateness of a robot’s voice

Abstract: Social robots have a recognizable physical appearance, a distinct voice, and interact with users in specific contexts. Previous research has suggested a 'matching hypothesis', which seeks to rationalise how people judge a robot's appropriateness for a task by its appearance. Other research has extended this to cover combinations of robot voices and appearances. In this paper, we examine the missing connection between robot voice, robot appearance, and deployment context. In so doing, we asked participants to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…The auditory performance results of the present study show promise for conducting the PICKA psychophysics tasks, insofar as the voice cue sensitivity and voice gender categorisation tests are concerned on Sam. Furthermore, our results contribute to the growing potential of using humanoid robots for both learning and testing applications [34-36, 75, 76], also for specific target groups and rehabilitation applications (e.g., [43,77,78]), and our general understanding of speech communication and voice perception in HRI, an increasingly relevant topic for social robots [1,13,79,80].…”
Section: Discussionmentioning
confidence: 66%
“…The auditory performance results of the present study show promise for conducting the PICKA psychophysics tasks, insofar as the voice cue sensitivity and voice gender categorisation tests are concerned on Sam. Furthermore, our results contribute to the growing potential of using humanoid robots for both learning and testing applications [34-36, 75, 76], also for specific target groups and rehabilitation applications (e.g., [43,77,78]), and our general understanding of speech communication and voice perception in HRI, an increasingly relevant topic for social robots [1,13,79,80].…”
Section: Discussionmentioning
confidence: 66%
“…The impact of matching the agent's look with its voice (congruency) on user-agent trust has been further studied, with contrary findings. For example, Torre et al [44] introduced an investment game to 120 participants to play with either a generous or a mean robot that switches from a human to a synthetic voice (or vice versa) in the middle of the game. The results indicate the importance of matching the voice with the look to form the first impression, which impacts the user's trust in the agent.…”
Section: Anthropomorphism and Congruencementioning
confidence: 99%
“…In a matching task, Torre, Latupeirissa, and McGinn [44] asked 60 participants to match one robot out of eight robots' pictures with a voice from a set of voices that varied in terms of gender and naturalness, for four different contexts: home, school, restaurant, and hospital. The results showed that the more mechanical the look of the robot, the greater the tendency for the robot to be matched with a synthetic voice, and that the matching was significantly different across the contexts.…”
Section: Anthropomorphism and Congruencementioning
confidence: 99%
“…This suggests that outcomes were related to the congruence of verbal and non-verbal features. In contrast, other studies failed to prove the importance of congruency on the desired outcome [13,14], which was explained by the dependency on the context such as education [15] and entertainment [16].…”
Section: Introductionmentioning
confidence: 96%